Portable Classrooms: Socioeconomic Context and Implications for Academic Achievement - Riveros, Augusto; Zhou, Chenyang (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2025)
Across many educational jurisdictions, school boards use portable classrooms to accommodate students in overcrowded schools. Despite their popularity, neither the socioeconomic contexts of their utilization nor their effects on academic achievement are well understood. This article expands the incipient literature on portable classrooms by reporting on a study that examined portable classroom use in the 27 largest school boards in Ontario, Canada. Through a combination of statistical strategies, this research reports on (a) the socioeconomic factors that increase the odds of having a high number of portable classrooms and (b) the factors associated with portable classroom use that affect academic achievement. Based on these findings, this article offers recommendations for policy and practice.